2002
DOI: 10.1103/physrevb.66.165321
|View full text |Cite
|
Sign up to set email alerts
|

Electronic structure ofInyGa1yAs

Abstract: We report photomodulated reflectance measurements of several intersubband transitions for a series of as-grown In y Ga 1Ϫy As 1Ϫx N x /GaAs multiple quantum well samples as functions of hydrostatic pressure ͑at room temperature͒ and temperature ͑at ambient pressure͒. The experimental results provide support for the effects of disorder due to different nearest-neighbor N-cation configurations. The quantum well transition energies obtained from the photomodulated reflectance spectra are fitted as a function of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0

Year Published

2003
2003
2008
2008

Publication Types

Select...
4
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 66 publications
(25 citation statements)
references
References 49 publications
2
23
0
Order By: Relevance
“…Our GaInNaAs/GaAs laser results are consistent with photo-modulated reflectance PR measurements of the QW transition energies performed on similar GaInNAs/GaAs QW wafer samples for which a strong sub-linear variation of band gap with pressure is observed over a wide pressure range [8]. Shan et al [9] report similar findings on GaInNAs/GaAs QWs for different nitrogen fractions using photomodulated transmission measurements under pressure.…”
Section: Pressure Effectssupporting
confidence: 87%
“…Our GaInNaAs/GaAs laser results are consistent with photo-modulated reflectance PR measurements of the QW transition energies performed on similar GaInNAs/GaAs QW wafer samples for which a strong sub-linear variation of band gap with pressure is observed over a wide pressure range [8]. Shan et al [9] report similar findings on GaInNAs/GaAs QWs for different nitrogen fractions using photomodulated transmission measurements under pressure.…”
Section: Pressure Effectssupporting
confidence: 87%
“…where the subscripts N, CB, and VB stand for nitrogen-resonant, conduction band, valence bands, respectively; V Nc describes the interaction between the N state and the CB edge, and P 0 (k) the coupling between the CB and various VBs as a function of the in-plane wavevector k. The N-related band offset parameters γ and α describe the movement of nitrogen resonant level and CB edge with content of nitrogen (x), while a parameter κ takes account of the variation of the VB offset between strained InGaN x As 1-x and GaAs, as a function of x [10]. By matching to the measured PR QW transition energies of the dilute-N InGaNAs MQWs as a function of pressure, with the theoretical model, we found that α = 1.55 eV, γ = 3.5 eV and κ = 3.5 eV (These parameters were estimated from tight-binding calculations, however they minor varied in order to obtain the best match between experiment and theory).…”
Section: Matching Theory With Experimentsmentioning
confidence: 99%
“…To achieve the best match only the layer compositions and thicknesses were varied within the uncertainties set by growth conditions (see Table 1), with standard minor-scaling of the other k · p parameters, as appropriate (we discuss this point below). A detailed description of the 10-band Hamiltonian has been given elsewhere [10]. Here, we use the following schematic form:…”
Section: Figmentioning
confidence: 99%
“…[58][59][60] The BAC model can be extended to treat ten bands (spindoubled conduction, valence, and nitrogen impurity bands) by modifying the 8-band k·p theory to include two extra spin-degenerate nitrogen states to describe the electronic band structure of GaNAs/GaAs and related heterostructures. [58][59][60][61][62] It was also argued that the electronic structure of GaNAs alloys is determined by interactions between nitrogen, X, L and Γ states 63,64 This provided more parameters to afford greater flexibility in fitting the experimental data. Although the BAC model does not consider anything more complicated than an interaction of randomly distributed localized nitrogen states with the extended states of the conduction band it properly describes all the main characteristics of the electronic structure of dilute nitrides.…”
Section: Band Anticrossingmentioning
confidence: 99%